Taxing away M&A: The effect of corporate capital gains taxes on acquisition activity - Lars P. Feld; Martin Ruf; Ulrich Schreiber; Maximilian Todtenhaupt; Johannes Voget (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik und Ordnungsökonomik, 2016)
Taxing capital gains is an important obstacle to the efficient allocation of resources because it imposes a transaction cost on the vendor which locks in appreciated assets by raising the vendor's reservation price in prospective transactions. For M&As, this effect has been intensively studied with regard to share-holder taxation, whereas empirical evidence on the effect of capital gains taxes paid by corporations is scarce. This paper analyzes how corporate level taxation of capital gains affects inter-corporate M&As. Studying several substantial tax reforms in a panel of 30 countries for the period of 2002-2013, we identify a significant lock-in effect. Results from estimating a Poisson pseudo-maximum-likelihood (PPML) model suggest that a one percentage point decrease in the corporate capital gains tax rate would raise both the number and the total deal value of acquisitions by about 1.1% per year. We use this result to estimate an efficiency loss resulting from corporate capital gains taxation of 3.06 bn USD per year in the United States.
Keywords: H25; G34; 330; corporate taxation; M&A; capital gains tax; lock-in effect